Comparative Study of Blood Pressure Measurement by Aneroid and Digital Manual Sphygmomanometer - Kakkad, Khyati M; Damor, Panchshila; Parmar, Bharat; Patel, Snehal; Prajapati, Vaishali; Dhivar, Nirali (National Journal of Community Medicine, 2016)
Introduction: After discontinuation of mercury sphygmomanometer, aneroid BP instrument and digital manual BP instrument are commonly used methods in clinical practice. This study was opted to compare the results of blood pressure measurement by aneroid and digital manual sphygmomanometer and determine the agreement between the two apparatus. Material and Method: After written consent, nursing students of Shardaben General Hospital were enrolled in the study. Their blood pressure was measured by both the methods at 5 minute interval in left upper limb. Their reading was documented and analyzed by appropriate statistical test. Results: Mean Systolic Blood pressure by digital and aneroid sphygmomanometer was 108.92+15.14 and 109.66+ 16.81 mm of Hg respectively. Mean Diastolic Blood pressure by digital and aneroid sphygmomanometer was 76.20+12.25 and 78.02+14.35 mm of Hg. By Bland –Altman test, the bias for mean systolic BP was 0.74(-9.0-10.5) and 1.8(_8.28_11.93) for mean diastolic BP by both the apparatus which is clinically non-significant. Conclusion: Blood pressure readings by digital manual and aneroid sphygmomanometer are comparable, so both the apparatus can be used interchangeably in clinical practice.